Study on biochemical polymorphism of two natural populations (Atlantic Morocco, and Roussillon) of elvers and eels Anguilla anguilla and comparison with two samples in culture. - Yahyaoui, A; Brusle, J; Pasteur, N (Actes de colloques. Ifremer. Brest [ACTES COLLOQ. IFREMER.]. 1985, 1983)
15 Types of allozymes were electrophoretically studied and variability of 24 genes analyzed and compared between Atlantic and Mediterrancean elvers (Anguilla anguilla ). No genetic difference was observed. The genetic homogenity agrees with a similar origin, the Sargasso Sea. Identity of enzymatic genes as found between different lots in culture and variation in growth was rather due to comportemental patternlike overcrowding than to genetic differences.